Revision for Solid‐Body Breakage of the 3D‐Printed Implant Following Joint‐Sparing Surgery: A Technical Note - Zhuangzhuang Li; Minxun Lu; Taojun Gong; Yong Zhou; Li Min; Yi Luo; Chongqi Tu (Orthopaedic Surgery, 2024)
Background The advent of three‐dimensional (3D)‐printed custom‐made implants has revolutionized orthopaedic surgery, particularly in limb‐ and joint‐sparing surgeries. However, clinical experience in the revision for 3D‐printed implant breakage is lacking, and the revision surgery remains challenging. This study reported the revision of proximal tibial prosthetic reconstruction necessitated by solid‐body breakage of a 3D‐printed implant, aiming to detail the surgical techniques and evaluate postoperative outcomes. Case Presentation A patient diagnosed with osteosarcoma underwent joint‐sparing surgery with a 3D‐printed implant, but implant breakage occurred during subsequent follow‐up. The initial implant was broken into two parts: the proximal implant breakage part (IBP) integrated with the host bone and the distal IBP left in the prosthetic component. Four revision protocols were devised, each based on one of the four hypothesis results of taking out the initial implant. A new custom‐made implant and a series of assistance devices (“positioning devices,” “drill devices,” “tap devices,” and “separator devices”) were specifically prepared for revision surgery. The proximal IBP was taken out from the host bone, but the distal IBP was not taken out from the initial prosthetic component. The patient received the new custom‐made implant for reconstruction, with the knee joint preserved. The patient recovered uneventfully after revision surgery and achieved satisfactory function. The Musculoskeletal Tumor Society was 28 at the last follow‐up. No complications were detected during the follow‐up period. Conclusion Comprehensive preoperative planning and preparation, enabling the surgeon to effectively address intraoperative challenges, are crucial for the successful revision of 3D‐printed implant breakage. It is feasible to re‐implant a 3D‐printed custom‐made implant, demonstrating satisfactory clinical and functional results.